On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). III. Acronicta lutea species group - Volynkin, Anton V.; Stüning, Dieter; Matov, Alexej Yu. (Zootaxa, 2016)
The present paper is the third in a series of articles on the genus Acronicta Ochsenheimer, 1816 (Volynkin et al. 2015; Volynkin 2015). Here we focus on the taxonomy of the Acronicta lutea species group, designating the lectotype of Acronicta lutea (Bremer & Grey, 1852), revising synonym status of Acronycta metaxantha funesta Draudt, 1950 and Pharetra leucoptera Butler, 1881, transferring Acronicta nigricans (Leech, 1900) to the subgenus Viminia Chapman, 1890 and introducing the new synonymy A. nigricans = Acronicta regifica Draudt, 1937 syn. n.